2007
DOI: 10.1080/08982100701528047
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Liver Fibrosis with Liposomes Targeted to Hepatic Stellate Cells

Abstract: Liver fibrosis is a chronic disease that results from hepatitis B and C infections, alcohol abuse or metabolic and genetic disorders. Ultimately, progression of fibrosis leads to cirrhosis, a stage of the disease characterized by failure of the normal liver functions. Currently, the treatment of liver fibrosis is mainly based on the removal of the underlying cause of the disease and liver transplantation, which is the only treatment for patients with advanced fibrosis. Hepatic stellate cells (HSC) are consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…However the role of NOX4 in ALD with or without co-existing fibrosis has not been sufficiently evaluated. Activated HSC are the major fibrogenic cell types in the liver6789 but they were also shown to have a significant immunomodulatory role by promoting homing and activation of tissue macrophages10 via the induction of C-C chemokine receptor type 2 (CCR2) in both the bile duct ligation (BDL) and carbon tetrachloride (CCl4) models of fibrosis11. CCL2, (also known as MCP1) was also described as a key mediator of inflammation in chronic ALD12, and CCL2 levels correlated with disease severity13.…”
mentioning
confidence: 99%
“…However the role of NOX4 in ALD with or without co-existing fibrosis has not been sufficiently evaluated. Activated HSC are the major fibrogenic cell types in the liver6789 but they were also shown to have a significant immunomodulatory role by promoting homing and activation of tissue macrophages10 via the induction of C-C chemokine receptor type 2 (CCR2) in both the bile duct ligation (BDL) and carbon tetrachloride (CCl4) models of fibrosis11. CCL2, (also known as MCP1) was also described as a key mediator of inflammation in chronic ALD12, and CCL2 levels correlated with disease severity13.…”
mentioning
confidence: 99%
“…Contrary to the conventional view that cirrhosis is an irreversible process, recent evidence has shown that even advanced fibrosis is reversible (Friedman, 2000;Arthur, 2002;Bataller & Brenner, 2005). At present, there is no efficient pharmaceutical intervention for liver fibrosis (Adrian, 2007;Li & Wang, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…The most common causes of liver fibrosis and cirrhosis include hepatitis B, hepatitis C, alcohol consumption, immune-mediated damage, genetic abnormalities, exposure to various drugs and toxic chemicals, and nonalcoholic steatohepatitis that is associated with diabetes and a metabolic syndrome (Dufour et al, 1993;Day, 2002;Adrian et al, 2007). The development of hepatic fibrosis reflects an alteration in the normally balanced processes of extracellular matrix (ECM) production and degradation (Friedman, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…26 Kamps et al first demonstrated that lipid-based drug carriers were selectively delivered to HSC in the fibrotic liver. 27,28 The liposomes from dilinoleoyl phosphatidylcholine (DLPC) showed to have antifibrotic properties, and the effects of targeted DLPC-containing liposomes on the activation of HSC and the progression of liver fibrosis were confirmed in BDL rats. Interestingly, DLPC containing liposomes strongly promoted the storage of glycogen in hepatocytes in fibrotic livers and caused accumulation of the liposomes in these cells within the fibrotic liver.…”
Section: A Hepatocytes-targeted Drug Deliverymentioning
confidence: 99%